The Influence of Location and Profit Sharing Level on Member’s Interest in Saving at KSPPS BMT UGT Nusantara Capem Tegaldlimo - Sholihah, Rovikatus; Fikri, Muhammad Kanzul (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to understand how much influence the location and profit sharing system have on the interest of the community to join as members of BMT UGT Nusantara Tegaldlimo Branch. This type of research uses quantitative research with an explanatory research approach. The data source used is primary data in the form of data from distributing questionnaires to members of BMT UGT Nusantara Tegaldlimo branch. Sampling with random sampling amounted to 60 respondents. Data analysis used in this study is validity analysis, reliability, classical assumption test (partial t test, simultaneous f test, and determination test) with the help of SPSS 23 software. The results of multiple linear regression analysis show that 1) Location partially has a significant effect on the interest of BMT UGT Nusantara Tegaldlimo branch members with a sig value of 0.00 <0.05; 2) profit sharing partially has a significant effect on the interest of BMT UGT Nusantara Tegaldlimo branch members with a sig value of 0.00 <0.05; 3) Location and profit sharing partially and simultaneously have a significant positive effect on the interest of BMT UGT Nusantara members in Tegaldlimo by 79.7%.